2006
DOI: 10.1097/01.yic.0000201496.23259.85
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia: who is at risk? Who is a case?

Abstract: Epidemiological studies have demonstrated a relevant increased risk of diabetes in schizophrenic patients who are treated with many atypical antipsychotics, irrespective of concomitant weight gain. Numerous case reports and some large retrospective cohort studies have documented an increased risk of diabetes with some second-generation antipsychotics (SGAs), leading different authors to identify patients on SGA as another high-risk group for diabetes in their review articles. An American consensus conference d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 40 publications
4
67
0
1
Order By: Relevance
“…The risk is significantly higher in patients started on SGAs. In line with published guidelines our results support the need for close monitoring of metabolic abnormalities and preferential use of metabolic neutral agents in this population as first line treatment option (Cohn and Sernyak, 2006;De Hert et al, 2006d;De Nayer et al, 2005;Marder et al, 2004;Newcomer, 2005Newcomer, , 2007a.…”
Section: Discussionsupporting
confidence: 75%
“…The risk is significantly higher in patients started on SGAs. In line with published guidelines our results support the need for close monitoring of metabolic abnormalities and preferential use of metabolic neutral agents in this population as first line treatment option (Cohn and Sernyak, 2006;De Hert et al, 2006d;De Nayer et al, 2005;Marder et al, 2004;Newcomer, 2005Newcomer, , 2007a.…”
Section: Discussionsupporting
confidence: 75%
“…Detailed guidelines before prescribing an atypical antipsychotic have been established (De Hert et al, 2006) and specific recommendations for safe monitoring of weight, blood pressure, blood glucose, and lipid profiles at the beginning and during antipsychotic treatment have been proposed (Newcomer, 2004;Franciosi et al, 2005;Meyer et al, 2005). Switching to an antipsychotic medication with a more appropriate risk/benefit profile has been recommended in patients who gain 5% of their baseline weight at any time during treatment (American Diabetes Association, 2004b).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, it is important to monitor any alteration in weight following a medication change. Pragmatic solutions for people with schizophrenia to prevent the development of diabetes should be proposed [49,50]. Baseline screening measures should be obtained before, or as soon as clinically feasible after, the initiation of any antipsychotic medication [1].…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…Fasting plasma glucose (and lipid levels and blood pressure as well) should also be assessed at regular intervals. We have shown that OGTT is able to detect abnormalities in glucose metabolism not shown by fasting measurements in numerous patients on antipsychotic medications [10,50]. For people who develop worsening glycemia while on antipsychotic therapy, it is recommended considering switching to an atypical antipsychotic medication that is associated with a lower risk of weight gain or diabetes [1].…”
Section: Clinical Recommendationsmentioning
confidence: 99%